2017
DOI: 10.1001/jamainternmed.2017.0936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alternate-Day Fasting on Weight Loss, Weight Maintenance, and Cardioprotection Among Metabolically Healthy Obese Adults

Abstract: IMPORTANCE Alternate-day fasting has become increasingly popular, yet, to date, no long-term randomized clinical trials have evaluated its efficacy.OBJECTIVE To compare the effects of alternate-day fasting vs daily calorie restriction on weight loss, weight maintenance, and risk indicators for cardiovascular disease. DESIGN, SETTING, AND PARTICIPANTSA single-center randomized clinical trial of obese adults (18 to 64 years of age; mean body mass index, 34) was conducted between October 1, 2011, and January 15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
550
2
30

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 504 publications
(617 citation statements)
references
References 30 publications
35
550
2
30
Order By: Relevance
“…The impact of intermittent fasting versus daily CR on glucoregulatory factors has been tested in a handful of clinical trials . Studies performed in metabolically healthy individuals generally demonstrate either superior improvements by fasting compared with daily restriction or no effect . For instance, Harvie et al and Hutchison and Heilbronn noted greater decreases in insulin resistance (~ 25%‐35% reductions) by intermittent fasting versus daily restriction (~ 15% reductions) after 2 to 6 months of intervention in healthy participants with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of intermittent fasting versus daily CR on glucoregulatory factors has been tested in a handful of clinical trials . Studies performed in metabolically healthy individuals generally demonstrate either superior improvements by fasting compared with daily restriction or no effect . For instance, Harvie et al and Hutchison and Heilbronn noted greater decreases in insulin resistance (~ 25%‐35% reductions) by intermittent fasting versus daily restriction (~ 15% reductions) after 2 to 6 months of intervention in healthy participants with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another form of dietary restriction that has gained attention in recent years is alternate‐day fasting (ADF) . ADF regimens generally consist of an ad libitum “feast day” alternated with a 25% energy intake “fast day.” Accumulating evidence has suggested that ADF and CR produce similar weight loss (6%‐8%) over 2 to 12 months in healthy adults with overweight and obesity . Research has also indicated that both diets are safe and well tolerated .…”
Section: Introductionmentioning
confidence: 99%
“…Time-restricted feeding resulted in dramatically lowered insulin levels and improved insulin sensitivity and β cell responsiveness, and lower blood pressure without altering circulating lipoprotein levels or markers of inflammation, without adverse effects. Taken together, while these clinical studies have demonstrated a beneficial effect of intermittent fasting in the setting of diabetes and pre-diabetes, it remains unclear if this strategy is sustainable (as the longest clinical trial lasted one year (220)) and if the beneficial effects are durable. It is also important to note that fasting strategies may be detrimental in individuals with type 1 diabetes which is characterized by primary beta cell failure and insulin deficiency, and provoke potentially fatal hypoglycemia; and therefore not a subject of clinical investigation.…”
Section: Intermittent Fasting As a Tool To Regulate Cardiometabolic Pmentioning
confidence: 99%
“…In general, this study supports the concept that once weekly intermittent fasting is safe and well tolerated in healthy individuals. Recently, ADF (25% of energy needs on fasting days, 125% on feast days) and chronic caloric restriction (75% of energy needs daily) were compared in a randomized controlled clinical trial of 100 patients (220). Overall, although both groups were associated with weight loss compared with control patients, there were no significant differences between ADF and chronic caloric restriction, although caloric restriction was better tolerated, with fewer drop outs.…”
Section: Intermittent Fasting As a Tool To Regulate Cardiometabolic Pmentioning
confidence: 99%
“…However, there is no clear definition provided of IER, which acts as an umbrella term that encompasses various dietary regimens. These include diverse interventions such as alternate day fasting (1 d of energy restriction followed by a day of ad libitum energy intake) , the 5:2 diet (2 d of energy restriction per week) and longer cyclic IER periods .…”
Section: Introductionmentioning
confidence: 99%